THE PRE-START SITUATION BETWEEN THE DIFFERENT PLAYING LINES OF THI-QAR UNIVERSITY FOOTBALL TEAM PLAYERS - Assistant Lecturer. Haider Mohsen Ali Al-Saadawi (European Journal of Humanities and Educational Advancements, 2023)
The state before the start is of great importance in refining the competition process among the players and preparing them appropriately to overcome the negative psychological state that will accompany the player from the beginning of the match. It highlights the importance of research in identifying the state before the start of the different playing lines in football and knowing which lines have the best level and working on Developing the positive aspects and addressing the negative aspects. The problem of the research lies in determining the condition before the start, neglecting it and not being familiar with it in the conditions of the match, and this reflects negatively on their skill, physical and physiological performance and creates a feeling of good psychological stability, which reflects negatively on the skill performance. The objectives of the research are to standardize the measure of the prestart condition of football players and to identify the pre-start condition of the Thi Qar University football team players according to the different lines of play